Two Conceptions of Practical Reasons - Hanisch, Christoph (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2016)
I discuss and compare Joseph Raz’s and Christine Korsgaard’s accounts of reasons for action. One fundamental disagreement separating the two approaches is the role that they assign to two central features of practical deliberation: Korsgaard assigns priority to identity-constituting practical principles, whereas for Raz reasons are the fundamental normative units. In the course of this comparison, two claims are defended: (1) Taking-up a realist stance vis-à-vis one’s reasons is a non-optional feature of one’s first-personal deliberative standpoint. This remains true even if this renders the workings of an agent’s reasons analogous to a placebo. (2) The motivational aspect of an agent’s reasons should not be conceived along causalist lines. Exploiting a thought by Hegel, I discuss an alternative conception of reasons’ temporal genesis and force—i.e., one that allows reasons for a particular action to emerge at a later point.